International benchmarking in electricity distribution: a comparison of French and German utilities - Astrid Cullmann; Hélène Crespo; Marie-Anne Plagnet (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
In this paper we present an international cross-country benchmarking analysis for utility regulation of France and Germany, the two largest electricity distribution countries in Europe. We examine the relative performance of 99 French and 77 German distribution companies operating within two different market structures. This paper applies several parametric benchmarking approaches to assess the relative technical efficiency of the utilities, such as deterministic Corrected Ordinary Least Squares (COLS) and Stochastic Frontier Analysis (SFA). Our base model uses the number of employees as a proxy for labor and network length as a proxy for capital as inputs. Units sold and the numbers of customers are considered as outputs. Our model variations and extensions analyze the effect of different characteristics of distribution areas (e.g. population density and the choice of investment in underground cable network). We find that utilities operating in urban areas feature higher efficiency scores and that investment in underground cables increase the technical efficiency of the distribution utilities.
Keywords: L94; L11; C40; 330; International benchmarking; electricity distribution; parametric efficiency analysis; Elektrizitätswirtschaft; Stromnetz; Technische Effizienz; Benchmarking; Schätzung; Deutschland; Frankreich